Cross Talk Between Macrophages and Cancer Cells in the Bone Metastatic Environment - Batoon, Lena; McCauley, Laurie K. (Frontiers in Endocrinology, 2021)
The skeleton is a common site for cancer metastases with the bone microenvironment providing the appropriate conditions for cancer cell colonization. Once in bone, cancer cells effectively manipulate their microenvironment to support their growth and survival. Despite previous efforts to improve treatment modalities, skeletal metastases remain with poor prognoses. This warrants an improved understanding of the mechanisms leading to bone metastasis that will aid development of effective treatments. Macrophages in the tumor microenvironment are termed tumor associated macrophages (TAMs) and their crosstalk with cancer cells is critical in regulating tumorigenicity in multiple cancers. In bone metastases, this crosstalk is also being increasingly implicated but the specific signaling pathways remain incompletely understood. Here, we summarize the reported functions, interactions, and signaling of macrophages with cancer cells during the metastatic cascade to bone. Specifically, we review and discuss how these specific interactions impact macrophages and their profiles to promote tumor development. We also discuss the potential of targeting this crosstalk to inhibit disease progression. Finally, we identify the remaining knowledge gaps that will need to be addressed in order to fully consider therapeutic targeting to improve clinical outcomes in cancer patients.